NEW MODEL FOR ESSENTIAL OILS HYDROEXTRACTION - Palomino l., Alfredo (2001)
The governing variables and parameters of the hydroextraction of essential oils are the bulk density of the extracting bed, the volumetric velocity of steam throughout the bed; the relative volatility of essential oils, the mechanical resistance of the vegetal matrix, and diffusional resistances and dispersion in the bed. This fact would divert the systern trom a classical vapor distillation analysis to a rather more complex system of separation, in which certainly the phase change velocity might be the process controlling step, but not necessarily in all the cases. Fortunately tor us, most of the above mentioned variables and parameters are linked with each other in such a way that the degree of freedom is reduced and we may simplify our analysis. Stating some assumptions and fixing some parameters, in this work we formulate a new hydroextraction model using saturated steam as extractant.